Examining the impact of financial development on energy production in emerging economies - Neil A. Wilmot; Ariuna Taivan (Journal of Risk and Financial Management, 2021)
Global energy production has been on the rise for many years, and reliance on traditional sources of energy remains strong. The extraction and production of energy can serve as an important avenue of growth, particularly for developing economies. To undertake such capital intensive project requires significant investment, and, intuitively, a well-functioning domestic financial system would be expected to aid in the growth of such industries. We investigate the relationship between financial development and energy production for 15 emerging countries, over the period of 1995-2017. After establishing the presence of a unit root, based upon panel data methods, a cointegrating relationship between financial development and energy production is confirmed. The results of the fully modified ordinary least squares (FMOLS) estimation establish a long run relationship in 11 of 15 countries in the sample. Panel Granger causality results provide a link between energy production and foreign direct investment (FDI), while such a link is absent for domestic credit. Policymakers should understand that development of the energy sector can provide an incentive for foreign firms to invest in emerging economics.
Keywords: 330; energy production; financial development; panel causality; panel cointegration